2012
DOI: 10.3233/cbm-2012-00270
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of volatile organic compounds biomarkers for lung cancer in exhaled breath, tissues and cell lines

Abstract: 23 VOCs, whose areas under curve (AUC) of receiver operating characteristic (ROC) > 0.60 and p < 0.01, were confirmed as the VOCs biomarkers for lung cancer. Three diagnostic models based on 23 VOCs could easily discriminate lung cancer patients from controls with 96.47% sensitivity and 97.47% specificity. However, the discrimination between early stage and later stage lung cancer was not very obvious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 32 publications
2
89
0
3
Order By: Relevance
“…Fresh stimuli were prepared each experimental day. The volatile components released by natural stimuli were analyzed by Gas Chromatograph Mass Spectrometer with the split-splitless injector (GCMS-QP2010/ PLUS, Shimadzu, Japan) (Konvalina and Haick, 2012;Wang et al, 2012). Because the concentrations of natural odors sent by the olfactometer (Med Associates, St. Albans, Vermont) were reduced due to the olfactometer design (Vincis et al, 2012), stimulus was presented directly to the rat snout.…”
Section: Odors Preparation and Stimulationmentioning
confidence: 99%
“…Fresh stimuli were prepared each experimental day. The volatile components released by natural stimuli were analyzed by Gas Chromatograph Mass Spectrometer with the split-splitless injector (GCMS-QP2010/ PLUS, Shimadzu, Japan) (Konvalina and Haick, 2012;Wang et al, 2012). Because the concentrations of natural odors sent by the olfactometer (Med Associates, St. Albans, Vermont) were reduced due to the olfactometer design (Vincis et al, 2012), stimulus was presented directly to the rat snout.…”
Section: Odors Preparation and Stimulationmentioning
confidence: 99%
“…Chen et al were able to determine a correlation between VOCs in the metabolic products of lung cancer cells and VOCs in the breath of lung cancer patients, some of whom had stage I and II disease [11]. In addition, in a later study, they confirmed similar results and determined the possibility to discriminate LC patients from healthy controls based on the presence of 23 VOCs that were used as biomarkers [12]. In our recent study, we have used dog plasma samples and have found six compounds that were significantly different in the cancer group (different cancers) in comparison with a cancer-free group of dogs [13].…”
Section: Introductionmentioning
confidence: 81%
“…Recent studies have identified small amounts of the metabolites specifically produced or consumed by the cell cultures [8][9][10][11][12]. For example, a total of nine compounds were found to be metabolized and additional twelve compounds were released by the cells in a study of HepG2 (hepatocellular carcinoma) cells [28]; eight compounds showed an increase and seven compounds showed a decrease in the headspace of A549 (lung carcinoma) cells compared with the control medium; four compounds were increased and seven compounds were consumed by the CALU-1 (non-small cell lung cancer, NSCLC) cell line [8].…”
Section: In Vitro Extraction Of Metabolites Excreted By Hela Cancer Cmentioning
confidence: 99%
“…As patients' quality of care gains more and more attention, lots of noninvasive disease diagnosis methods are proposed [1,2].…”
Section: Introductionmentioning
confidence: 99%